CusS-CusR Two-Component System Mediates Tigecycline Resistance in Carbapenem-Resistant Klebsiella pneumoniae - Chen, Dongjie; Zhao, Yunan; Qiu, Yanqin; Xiao, Liying; He, Huaqiang; Zheng, Dongmei; Li, Xiaoqin; Yu, Xiaoli; Xu, Nengluan; Hu, Xinlan; Chen, Falin; Li, Hongru; et al. (Frontiers in Microbiology, 2020)
Background: The increase in carbapenem-resistant Klebsiella pneumoniae (CRKP) is a serious public health concern, especially the emergence of tigecycline-resistant K. pneumoniae (KP). However, the underlying mechanism of tigecycline resistance is unclear. In this study, we evaluated the role of the CusS-CusR two-component system (TCS), which is associated with copper/silver resistance, in tigecycline resistance in CRKP. Methods: Following the in vitro evolution of tigecycline-resistant K. pneumoniae (KP), the minimum inhibitory concentrations of tigecycline were determined by the micro-broth dilution method. RNA sequencing and data analysis were performed to identify differentially expressed genes. Quantitative PCR (qPCR) was performed to verify the genes of interest. Genes associated with tigecycline resistance, such as ramR, tex (T), and tet (A), were detected by PCR, and then mutants were confirmed by sequencing. Additionally, the efflux pump-associated genes soxS, oqxA, oqxB, acrE, and acrF were also analyzed by qPCR. Results: Nine strains of KP were evaluated in our study. Strains A2 and A3 were evolved from A1, B2 and B3 were evolved from B1, and C2 and C3 were evolved from C1. The tigecycline minimum inhibitory concentrations for A1, B1, and C1 were 0.5 μg/mL; those for A2, B2, and C3 were 16.0 μg/mL; and those for A3, B3, and C3 were 32.0 μg/mL. RNA-sequencing and qPCR confirmed that the differentially expressed genes cusE, cusS, cusR, cusC, cusF, cusB, and cusA showed higher expression in C2 and C3 than in C1. Genes related to the efflux pump acrAB-tolC showed higher expression in B2 and B3 than in B1. No mutants of ramR, tex (T), or tet (A) were detected. SoxS, oqxA, oqxB, acrE and acrF did not show increased expression in any groups. Conclusion: In addition to its primary function in resistance to copper/silver, the CusS-CusR two-component system is associated with CRKP resistance to tigecycline.